2012
DOI: 10.1093/plankt/fbs028
|View full text |Cite
|
Sign up to set email alerts
|

Mesozooplankton and particulate matter responses to a deep-water frontal system in the southern California Current System

Abstract: We analyzed the abundance of mesozooplankton and suspended particulate matter across the deep-water "A-Front" in the southern sector of the California Current System. We characterized the A-Front with two novel devices, a free-fall Moving Vessel Profiler (MVP) and an Underwater Vision Profiler 5 (UVP5), together with quantitative bongo samples analyzed by ZooScan. The MVP permitted real-time visualization of vertical density structure, chlorophyll a fluorescence and particle size structure (from a laser optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 45 publications
3
94
2
Order By: Relevance
“…The LOPC does not give any taxonomic information, and nets are not suited to capture marine snow or fragile zooplankton. Therefore, it is often unclear if transparent particles are marine snow or transparent zooplankton, and this varies in all likelihood regionally and seasonally (Ohman et al, 2012;Basedow et al, 2013). To separate zooplankton from other particles we followed the method developed by Espinasse et al (2017) that indicates the ratio of zooplankton to detritus among small (SEPs) and large (MEPs) particles by analyzing two simple indicators, the percentage of MEPs in all counts, and the mean AI of MEPs.…”
Section: Analyses Of Zooplankton Distributionsmentioning
confidence: 99%
“…The LOPC does not give any taxonomic information, and nets are not suited to capture marine snow or fragile zooplankton. Therefore, it is often unclear if transparent particles are marine snow or transparent zooplankton, and this varies in all likelihood regionally and seasonally (Ohman et al, 2012;Basedow et al, 2013). To separate zooplankton from other particles we followed the method developed by Espinasse et al (2017) that indicates the ratio of zooplankton to detritus among small (SEPs) and large (MEPs) particles by analyzing two simple indicators, the percentage of MEPs in all counts, and the mean AI of MEPs.…”
Section: Analyses Of Zooplankton Distributionsmentioning
confidence: 99%
“…Ecosystem processes at fronts have attracted the interest of many previous investigators in the California Current System (e.g., Mackas et al, 1991;Haury et al, 1993;Venrick, 2000). A recent study in the CCE study domain revealed striking ecological changes at an oceanic frontal system (Landry et , Synechococcus, and total diatoms (taylor et al, 2012); bacterial carbon production rate (Samo et al, 2012); photograph of composition of net tows from 100-0 m (202 µm mesh); vertically averaged abundance of nauplii (free-swimming copepod larvae) per adult copepod and total calanoid copepods (Ohman et al, 2012a); vertical sections of acoustically derived estimates of euphausiid and fish acoustic backscatter (lara-lopez et al, 2012). in panel (d), stations are oriented from south (left) to north (right).…”
Section: Four Centr Al Mechanismsmentioning
confidence: 99%
“…Vertical band delineates the front. Modified from the cover of the Journal of plankton research, September 2012 (see Landry, Ohman et al, 2012) maximum in diatoms was associated with elevated nitrate fluxes , peak phytoplankton variable fluorescence (Chekalyuk et al, 2012), elevated bacterial production (Samo et al, 2012), increased concentrations of organic aggregates (Ohman et al, 2012a), elevated abundance of calanoid copepods and of naupliar recruitment (Ohman et al, 2012a), and increases in both euphausiid and pelagic fish populations (Lara-Lopez et al, 2012). We hypothesize that such ecological "hot spots, " while …”
Section: Four Centr Al Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations